ASSESSMENT OF THE ADEQUACY OF BUSINESS EDUCATION CURRICULUM CONTENT FOR THE ACQUISITION OF OFFICE TECHNOLOGY AND MANAGEMENT AND ENTREPRENEURSHIP SKILLS ACQUISITION IN COLLEGES OF EDUCATION IN EDO AND DELTA STATES (NAU Journal of Technology and Vocational Education, 2024)
The study sought to assessthe adequacy of business education curriculum content for theacquisition of office technology and management and entrepreneurship skills acquisition incolleges of education in Edo and Delta States. Two research questions were raised and fournull hypotheses were tested. Descriptive survey research was adopted for the study. The entirepopulation of 120 business educators were studied without sampling. A structured andvalidated two-point checklist was used for data collection. Since, the National Commission forColleges of Education (NCCE) Benchmark inventory is a standard checklist, the checklist wasnot subjected to reliability procedures because the checklist is already validated andstandardized. Mean and standard deviation were used to answer the research question,’while ttest and Analysis of Variance (ANOVA) were used to test the null hypotheses. Findings of thestudy revealed that 68 contents of the curriculum are adequate and 46 contents are notadequate for the acquisition of office technology and management skills. 11 contents of businesseducation curriculum are adequate and four contents are not adequate for the acquisition ofentrepreneurship skills. The study further disclosed that bbusiness educators based on theiryears of experience and location did not differ significantly on their mean ratings on theadequacy of business education curriculum content for the acquisition of office technology andmanagement skills and entrepreneurship skills among students. It was recommended amongothers that business educators in Colleges of education should periodically invite officetechnology and management experts and successful entrepreneurs to provide businesseducation students with first hand business experiences and practical workplace skills requiredin the business world.
Keywords: Assessment, College of Education, Business education, Office technology and management skills, and Entrepreneurship skills